Ontologies and Technologies for Integrating and Accessing Digital Cultural Heritage: Lithuanian Approach - Varnienė-Janssen, Regina; Šermokas, Albertas (Information & Media, 2020)
Web technologies are the key for the implementing and ensuring the full range of user needs in the digital age. On the other hand, the issue of unified representation of digital content from diverse memory institutions in order to ensure semantic integrity still remains a matter of urgency. Semantic interoperability of information and data is essential in an integrated system. In this paper, we analyze and describe an ontology-based metadata interoperability approach and how this approach could be applied for memory institution data from diverse sources which do not support ontologies. In particular, we describe the use of the CIDOC CRM ontology as a mediating schema within Lithuania’s Information System of the Virtual Electronic Heritage (hereinafter ”VEPIS”) The paper introduces the role of the CIDOC CRM based Thesaurus of Personal Names, Geographical Names and Historical Chronology (hereinafter “BAVIC”), which operates as a core ontology within VEPIS by allowing to understand things and relationships between things as well as identify the time and space of things. The paper also focuses on trust of the cultural information on the Web. Users make trust judgments based on provenance that may or may not be explicitly offered to them. In particular, we describe how provenance is managed within digital preservation and access processes within VEPIS and define whether this management meets the W3C Provenance Incubator Group’s Requirements for Provenance on the Web. The paper is based on the results of the research initiated in 2018–2019 at the Faculty of Communication and the Faculty of Mathematics and Informatics of Vilnius University by authors of this paper.